Analisis Jaringan Komunikasi dalam Alih Teknologi Pasca Panen Ubi Kayu di Desa Sabulakoa, Kecamatan Tinanggea, Kabupaten Konawe Selatan - Wunawarsih, Ima Astuty; Suriana, Suriana (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
The aims of this research are to know: 1) The communication network in post-harvest technology of cassava; 2) The role of members on the communication network in post-harvest technology of cassava; 3) The main information by each member of group communication in post-harvest technology of cassava. The number of samples is 23 person by census method. The data were tabulated and further analyzed by descriptive qualitative. Knowing the correlation each member which involved in the communication network are using sociometric arranged in a matrix, will be formed sociogram (netting system). Results of that research has shown: 1) Communication network is formed by cassava is highly varied: The majority of respondents getting information by 1-2 sources as many as 86,96%, and 13,04% respondent getting information of three source; 2) Each members a group on communication network of post-harvest technology of cassava has different role, such as: (a) Agriculture of extension (PPL) as outliers (isolated), (b) a farmer as liaison, (c) Community leaders as a bridge, and (d) Fellow farmers as a star; and 3) The information conveyed by each member in the communication network of information related to post-harvest technology of cassava storage techniques that are complementary. The information is including materials are using to store, best storage, and storage procedures.